Validity of E-Module Based on Problem Based Learning Integrated Demonstration Video and Science Literacy - Aulia, Annisa; Hardeli, Hardeli (IJIS Edu : Indonesian Journal of Integrated Science Education, 2022)
The time of mechanical insurgency 4.0 is a period of digitalization in different areas particularly within the field of instruction so it takes educating fabric that can increment understudy movement in learning. This type of research is educational design research using the Plomp model. This model consists of three steps: (1) preliminary research, (2) prototyping, and (3) assessment phase. The research instrument used observation sheets, questionnaires, and learning outcomes tests. The e-module was validated by six construct experts and three content experts. This inquires about points to create an e-module of electrolyte and nonelectrolyte solutions based on problem-based learning integrated demonstration videos and scientific literacy and decide the level of validity of created e-module. This sort of investigation is instructive plan inquire about utilizing the plomp model. The appraisal rebellious utilized were perceptions sheets, surveys, and learning results tests. The e-module was approved by five validators, to be specific the build validator and the substance validator. The comes about of the validity of the e-module develop gotten Aiken’s V normal esteem of 0.85 with a substantial category, and the validity of the e-module substance gotten a normal CVI esteem of 1 with a substantial category. Based on the results of the study, it was concluded that the problem-based learning e-module of electrolyte and nonelectrolyte solutions integrated with demonstration videos and scientific literacy developed was valid.